2020
DOI: 10.1017/s0144686x20000550
|View full text |Cite
|
Sign up to set email alerts
|

Internet use, social isolation and loneliness in older adults

Abstract: The aim of this study was to explore associations between internet/email use in a large sample of older English adults with their social isolation and loneliness. Data from the English Longitudinal Study of Ageing Wave 8 were used, with complete data available for 4,492 men and women aged ⩾ 50 years (mean age = 64.3, standard deviation = 13.3; 51.7% males). Binomial logistic regression was used to analyse cross-sectional associations between internet/email use and social isolation and loneliness. The majority … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 84 publications
6
21
0
1
Order By: Relevance
“…Overall, internet use was high and frequent in our sample. This is in line with recent research findings (Stockwell et al 2020;Vulpe and Crăciun, 2020) and findings of König et al (2018) and indicates that Belgian older adults are also amongst the most frequent internet users in Europe. The most frequently executed activities were navigating the web, sharing email and online banking, whereas tele-communication, online shopping and consulting e-government services were the least common.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Overall, internet use was high and frequent in our sample. This is in line with recent research findings (Stockwell et al 2020;Vulpe and Crăciun, 2020) and findings of König et al (2018) and indicates that Belgian older adults are also amongst the most frequent internet users in Europe. The most frequently executed activities were navigating the web, sharing email and online banking, whereas tele-communication, online shopping and consulting e-government services were the least common.…”
Section: Discussionsupporting
confidence: 92%
“…The most frequently used devices by older adults are mobile phones (91-92%), followed by computers (61-86%) and tablets (39%) (Hernández-Encuentra et al 2009;LaMonica et al 2017). A recent study by Stockwell et al (2020) revealed a relationship between use frequency and ICT device, with the higher frequent users more often using smartphones and tablets as compared to less frequent users, who tend to use computers more often. Sharing email, communicating with family members or friends, reading newspapers and online banking are the most frequent internet activities undertaken by older adults (Chang et al 2015;Choi and DiNotto 2013;Hernández-Encuentra et al 2009;König et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…video telemedicine visits) due to inexperience with technology or physical disability. 44 Consistent with prior research 31,45 and likely a function of electronic survey administration, we found high levels (∼85%) of social media engagement, with no increased risk for loneliness. Our findings suggest there is a large segment of the older adult population for whom digital media-based interventions may be effective for mitigating and alleviating loneliness.…”
Section: Discussionsupporting
confidence: 89%
“…Social isolation was also adjusted for using a previously used ELSA approach [ 18 , 22 , 23 ] whereby one point was allocated for each of the following: living alone, having less than monthly contact with each of children, other members of the family and friends [in person/ telephone], and not being a member of organisations. Scores were summed to provide a social isolation index ranging from 0 to 5, which was then dichotomised, as in previous investigations, to distinguish between low [< 2] and high [≥ 2] levels of social isolation [ 18 , 22 , 23 ]. For the current analysis isolation data from waves 4 to 8 was included.…”
Section: Methodsmentioning
confidence: 99%